Prenatal diagnosis of 1408 foetuses at risk of DMD/BMD by MLPA and Sanger sequencing combined with STR linkage analysis - Chunxiao Hua; Lina Liu; Xiangdong Kong (BMC, 2023)
Abstract Objective This study is a retrospective analysis of the prenatal genetic diagnosis results of 1408 foetuses at high risk of DMD/BMD to provide information for clinical genetic counselling. Background Duchenne muscular dystrophy (DMD) is a severe neuromuscular disorder characterized by skeletal and cardiac muscle weakness. With the deepening of disease research, some treatments have been applied in clinics. Therefore, early and accurate prenatal diagnosis can inform pregnancy choices for high-risk families. Methods A total of 1316 unrelated DMD/BMD families with confirmed genetic diagnoses were recruited from the Genetic and Prenatal Diagnosis Center of the First Affiliated Hospital of Zhengzhou University. Prenatal diagnosis of 1408 high-risk foetuses was performed by MLPA and Sanger sequencing combined with STR linkage analysis for all families. Results Among the 1316 families, large deletions, duplications, and small variants of the DMD gene accounted for 70.4% (927/1316), 8.2% (108/1316), and 21.4% (281/1316), respectively. Among 1316 mothers, 863 (65.6%) were carriers, and 453 (34.4%) were not carriers. The rate of de novo variants was 34.4% (453/1316) in our study. In addition, gonadal mosaicism was observed in 11 pregnant females. Prenatal diagnosis was provided for 1408 high-risk foetuses; 282 foetuses were identified as male patients, 219 foetuses were female carriers, and the remainder had normal genetics. The results of prenatal diagnosis were consistent with the results of follow-up. Conclusions Accurate and rapid prenatal diagnosis can be achieved using MLPA, Sanger sequencing, and STR linkage analysis. Furthermore, germline mosaicism in DMD should not be ignored; considering this, a prenatal diagnosis for all pregnant women with a family history of DMD/BMD regardless of whether they carried disease-causing variants is proposed. Genetic counselling and targeted prenatal diagnosis will continue to be a cornerstone of DMD/BMD family management in the future.